An outbreak of Q fever associated with parturient cat exposure at an animal refuge and veterinary clinic in southeast Queensland - Jonathan A. Malo; Candice Colbran; Megan Young; Bhakti Vasant; Kari Jarvinen; Kerri Viney; Stephen B. Lambert (Elsevier, 2018)
Abstract Objective: To determine the source of a Q fever outbreak in humans at an animal refuge and veterinary clinic in southeast Queensland from October to December 2016. Methods: Case interviews and a retrospective cohort study of animal refuge and veterinary clinic staff using a self‐administered questionnaire related to clinical history of Q fever, Q fever vaccination status and workplace activities during the exposure period. Results: Seven cases (six confirmed, one probable) were identified. Forty‐three questionnaires were completed (92% response rate). Workplace activities associated with the greatest risk of illness were the disposal of deceased cats or dogs (RR, 14.0; 95%CI, 1.9-104.1) and participating in euthanasia of cats or dogs (RR, 4.6; 95%CI, 1.3-16.9). Five feline birthing events occurred at the animal refuge from 25 September to 19 October 2016, each with subsequent euthanasia of the queen cat and litter. All cases had likely exposure to a specific queen cat and her litter that were euthanised the same day as the birthing event. Conclusions: A parturient cat was the most likely source of the outbreak. Implications for public health: Occupational groups and others with regular exposure to feline or canine parturient products should receive Q fever vaccine.